The Effectiveness of the Kangaroo Method and Cloth Swaddling to Increase the Body Temperature of Newborns Baby and Prevent Hypothermia - Ni Putu Eka Budi Sulistiyawati; Ana Mariza; Sunarsih Sunarsih; Nita Evriana Sari (Universitas Malahayati Lampung, 2023)
ABSTRACT The coverage of presentations of babies who received exclusive breastfeeding in Indonesia was 61.33%. The government has targeted the achievement of exclusive breastfeeding in Indonesia by 80%, but this has not been achieved until now. The purpose of this study was to determine the factors related to exclusive breastfeeding to infants aged 7 to 12 months. This type of research is quantitative Analytical Survey Design with a cross-sectional approach. The maternal population had babies aged 7-12 months 78 with the number of samples taken by 30 respondents carried out by accidental sampling from July to August. Questionnaire research instruments and data analysis using the pearson chi-square test. The results of moderate education of breastfeeding there are often 7 (23.3%) higher education breastfeeding not often 13 (43.4%), breastfeeding is often 10 (33.3%). Maternal age 20-35 years exclusive breastfeeding 5 (16.7%) not exclusive breastfeeding 14 (46.7%), age 35 years exclusive breastfeeding 8 (26.7%), non-exclusive breastfeeding 3 (10.0%). Not working breastfeeding is often 16 (53.3%), working mothers give breast milk not often 13 (43.3%), breastfeeding is often there as much as 1 (3.3%). Sources of information on breastfeeding are not often 2(6.7%), breastfeeding is often 8 (26.7%). p-value = 0.027( α 0.05) there is an educational relationship, p-value = 0.000( α 0.05) there is a relationship, p-value = 0.083( α 0.05) there is a relationship of information sources, p-value = 0.201( α 0.05) which means there is no relationship between MCH book users, p-value = 0.77( α 0.05). There is no relationship of the role of health workers. In conclusion there is an influence of factors related to exclusive breastfeeding in infants. The researcher's advice provides further knowledge for mothers to still give breast milk rights to babies. Keywords: Exclusionary Breast Milk, Baby, Influencing Factors ABSTRAK Cakupan presentasi bayi yang mendapat ASI eksklusif di Indonesia adalah sebesar 61,33%. Pemerintah telah menargetkan pencapaian ASI Ekslusif di Indonesia sebesar 80%, namun hal itu masih belum tercapai hingga saat ini. Tujuan dari penelitian ini yaitu untuk mengetahui faktor yang berhubungan dengan pemberian ASI ekslusif kepada bayi usia 7sampai12 bulan. Jenis penelitian ini yaitu kuantitatif Rancangan Survei Analitik dengan pendekatan cross sectional. Populasi ibu memiliki bayi usia 7-12 bulan 78 dengan jumlah sampel yang di ambil 30 responden dilakukan secara accidental sampling dari juli sampai agustus. Instrumen penelitian kuesioner dan analisis data menggunakan uji pearson chi-square. Hasil pendidikan sedang pemberian asi sering ada 7 (23,3%) pendidikan tinggi pemberian asi tidak sering 13 (43,4%), pemberian asi sering 10 (33.3%). Usia ibu 20-35 tahun asi ekslusif 5 (16,7%) tidak asi ekslusif 14 (46,7%), usia 35 tahun asi secara ekslusif 8 (26,7%), yang tidak asi ekslusif 3 (10,0%). Tidak bekerja pemberian asi sering 16 (53,3%), ibu bekerja memberikan asi tidak sering 13 (43,3%), pemberian asi sering ada sebanyak 1 (3,3%). Sumber informasi pemberian asi tidak sering 2(6,7%), pemberian asi sering 8 (26,7%). p-value = 0,027( α 0,05) ada hubungan pendidikan, nilai p-value = 0,000( α 0,05) ada hubungan, nilai p-value = 0,083( α 0,05) ada hubungan sumber informasi, nilai p-value = 0,201( α 0,05) yang artinya tidak ada hubungan antara pemanfaatn buku KIA, p-value = 0,77( α 0,05) tidak ada hubungan peran petugas kesehatan. Ada pengaruh faktor yang berhubungan dengan pemberian asi ekslusif pada bayi. Saran peneliti memberikan pengetahuan lebih lanjut untuk ibu agar tetap memberikan hak asi pada bayi. Kata Kunci: ASI Ekslusi, Bayi, Faktor yang Mempengaruhi